An Innovative, Interdisciplinary Intervention for Justice-involved Emerging Adults - Courtney M Holmes; Jeff Ciak; Marianne Lund; Zehra Sahin Ilkorkor; Grace Kye; Miguel King; Karen Akom; Sarah Jane Brubaker; Molly Hyer; Gary Cuddeback (Teaching and Supervision in Counseling, 2025)
Interdisciplinary collaboration is an effective training model for counselors in training. As it is becoming increasingly likely that counselors will work in multidisciplinary teams post-graduation, engagement in clinical and research intervention teams is essential to promote learning. Benefits for counseling students include the development of self-efficacy, cultural humility, research skills, counseling skills, and interdisciplinary communication and collaboration skills. This article will discuss a federally funded, interdisciplinary intervention for justice-involved emerging adults that provides supported employment, trauma-informed mental health counseling, and peer support interventions. We will outline the interventions, structure of the project, as well as research and assessment outcomes. Future directions related to promoting collaborative interventions and addressing the research to practice gap in counselor education will be discussed.
Keywords: interdisciplinary; counselor education; justice-involved young adults; supported employment; trauma-informed care